INTERLACEMENTS: ALLOPHILIA AND FIGURATIONS OF THE OUTSIDER IN KOKOSCHKA’S DOLL BY AFONSO CRUZ - Simões, Maria João (2022)
In several novels by Afonso Cruz, the figurative process involved in constructing characters is achieved by means of a complex shifting back and forth between the individual and the collective, without either one erasing the other. This is the case in Kokoschkas Doll, where the most important figures are not stock characters who represent certain types of individuals but are instead very singular figures with traits that are not only unique but even outlandish or improbable. Nevertheless, this does not mean that their fractured identities are not signs that carry profound connotations which contribute to (and are part of) a broader representation of traumatic historical social conditions and periods of conflict.